(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
There are shown improvement of vertical butting earthquake proof of the large-panel buildings in this paper. Offered non-welding and non-curb butting join has some advantage in contrast with other butting by join. On noted constructive decision is received patent for invention. For ensuring raised carrying abilities and perceptions of the seismic loads 8-9 rate, butting in 1/4 parts of the height is supplied by pipe with located on her stressed spiral winding of reinforcement. Herewith volume of the monolithic concrete decreases on 3/4 and curb of the work. Given variant of butting joining the panels are justified in economical attitude. At economy of the main building materials-cement and metal forms before 10 % of the average. Besides shortcut gage applicable profiles worker armature in vertical butting of the large-panel buildings and dress before 4-h units (on attitude design). Such decision vertical butting allows the construction of the large-panel buildings seismicity 8-9 rates.